Impactos da institucionalização na saúde mental do idoso - Dantas, Luã Carlos Valle [UNESP] (2013)
The present work proposes an analysis of the conditions of the elderly on a Brazilian context, focusing the institutionalized elders and the nuances of the institutionalization process on their mental health. Bibliographical analysis and participative observation were used as method. On the discussion, the present work demonstrates that the institutionalization have harmful effects to the elders, at their mental health and from this, proposes a multidisciplinary view of the process.